2018
DOI: 10.3390/nano9010035
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Silica-gold Films for Straightforward, Highly Reproducible Monitoring of Mercury Traces in Water

Abstract: Trace-level detection of mercury in waters is connected with several complications including complex multistep analysis routines, applying additional, harmful reagents increasing the risk of contamination, and the need for expensive analysis equipment. Here, we present a straightforward reagent-free approach for mercury trace determination using a novel thin film sampling stick for passive sampling based on gold nanoparticles. The nanoparticles supported on a silicon wafer and further covered with a thin layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 27 publications
3
13
0
Order By: Relevance
“…Therefore, the development of a more sophisticated structure of the active film covered by a protective layer was necessary. The latter has already been shown in a recent work of the authors, where we reported about mesoporous silica–gold films for efficient chemical-free Hg trace analysis [ 34 ]. Parameters found optimum for mercury accumulation in terms of film thickness and mesopore diameter in that study are used as design targets for the current study.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…Therefore, the development of a more sophisticated structure of the active film covered by a protective layer was necessary. The latter has already been shown in a recent work of the authors, where we reported about mesoporous silica–gold films for efficient chemical-free Hg trace analysis [ 34 ]. Parameters found optimum for mercury accumulation in terms of film thickness and mesopore diameter in that study are used as design targets for the current study.…”
Section: Introductionsupporting
confidence: 66%
“…These containers were filled with either 6 mL or 8 mL of a Hg 2+ -containing aqueous solution, and accumulation was performed at room temperature on an orbital shaker at 230 rpm for 5 min. These parameters were tested in our previous study and found to be optimum [ 34 ]. Hg concentrations ranged from 5 to 25 ng L −1 .…”
Section: Methodsmentioning
confidence: 99%
“…Mesoporous silica films are of large interest in applications such as sensing, catalysis, and drug delivery [1,2,3,4,5,6]. Their large surface area, tunable pore characteristics, and versatile surface functionality are attractive features.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the contributions that are grouped in this Special Issue provide a good idea of the directions in which the field is moving. The contributions range from the synthesis of special nanosystems [1,2,3] to their utilization for sensing [4,5,6,7] and magnetic resonance imaging [8,9], surface recognition [10], and bioapplications [11].…”
mentioning
confidence: 99%
“…Mercury is well known for its neurotoxicity. To tackle the problem of its detection, Leopold, Linden et al [6] present a straightforward reagent-free approach for mercury traces determination using a novel thin film for passive sampling based on gold nanoparticles. Dissolved mercury ions are extracted from a water sample, e.g., river water, by incorporation into the gold matrix in a diffusion-controlled manner.…”
mentioning
confidence: 99%